Record highest sensitivity of -28.0 dBm at 10 Gb/s achieved by newly developed extremely-compact superlattice-APD module with TIA-IC - Sato, K.; Hosoda, T.; Watanabe, Y.; Wada, S.; Iriguchi, Y.; Makita, K.; Shono, A.; Shimizu, J.; Sakamoto, K.; Watanabe, I.; Mitamura, K.; Yamaguchi, M. (Optical Fiber Communications Conference: Post Conference Digest, 2002)
The highest receiver sensitivity of -28.0 dBm was achieved by a combination of a superlattice APD with a large gain-bandwidth product (110 GHz) and a properly designed high-gain (63 dB/spl Omega/) HJFET TIA-IC. Greater than -26.5 dBm sensitivity was also successfully demonstrated over the wide wavelength range covering C- and L- bands and temperature range of 0 to 70 degC. by a successfully designed extremely small package with dimensions of 9.8 /spl times/ 7.5 /spl times/ 4.0 mm/sup 3/ (only 0.3 cc).